2009
DOI: 10.1097/bth.0b013e3181ac9183
|View full text |Cite
|
Sign up to set email alerts
|

The Glabrous Palmar Flap

Abstract: We devised a new flap using the palmar cutaneous branch of the superficial radial artery proximally and anastomosed with a cutaneous perforator of the superficial palmar arch distally. We named our flap "the volar glabrous palmar flap." The flap was used both as a free flap and as a reverse-flow island flap. Thirty-six patients with volar hand defects (24 digits, 7 palms, and 5 first web space) were reconstructed with this flap. The flap was used as a proximally based free flap in 15 patients and was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…For experienced surgeons, it usually takes approximately 30 min for harvesting RASPB flap and another 1 h for anastomosis of digital artery, superficial vein, and digital nerve. Therefore, we can usually complete all the procedure within 2 h. Previously, there are have been several studies reporting the clinical effects of this flap for reconstructing finger defects [57]. But these studies only include less than 15 cases and reported limited experience of just a single hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For experienced surgeons, it usually takes approximately 30 min for harvesting RASPB flap and another 1 h for anastomosis of digital artery, superficial vein, and digital nerve. Therefore, we can usually complete all the procedure within 2 h. Previously, there are have been several studies reporting the clinical effects of this flap for reconstructing finger defects [57]. But these studies only include less than 15 cases and reported limited experience of just a single hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The RASPB usually divides from the radial artery at 1.0–2.0 cm proximal to the distal wrist crease [6], with mean diameter at its original site being 1.2 mm (range, 1.0–1.4 mm), which is similar to the diameter of the digital artery [7]. The RASPB then descends along the ulnar side of scaphoid tubercle [8] and commonly goes together with one or two venae comitantes [9].…”
Section: Methodsmentioning
confidence: 99%
“… Reference Sample Size Immediate Complications Late complications Follow-up (months) Outcome Sensory recovery (2PD) Omokawa et al 6 1996 1 None None 10 No data 8mm Omokawa et al 7 2002 6 Distal necrosis (1) - healed spontaneously None 61 Acceptable cosmetic result of donor site 6,4,6mm in innervated flaps. Orbay et al 8 2009 21 Distal necrosis - (1) in 76M, Dupuytrens, healed spontaneously. None 24 Excellent cosmetic and functional 6mm for 1 case Seyhan T 9 2009 7 Distal necrosis (1) in a 70-year old.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the older generation of free flaps, although avoiding the second stage, take longer to perform, have the same problem of subcutaneous fat and will swell significantly, so, require secondary thinning of the flap later. The newer generation of free flaps includes some, such as the instep fla[1011] [Figure 10] and the newer version of free venous flap[1214] [Figure 11] and the glabrous palmar flap[15] which have little subcutaneous fat, largely, but not entirely, avoid this problem. The venous flaps return again to the flexor aspect of the wrist as a donor site for thin skin.…”
Section: Skin Deficiency In the Flexor Aspect Of The Fingermentioning
confidence: 99%